2022
DOI: 10.1007/s42773-022-00164-z
|View full text |Cite
|
Sign up to set email alerts
|

A quantitative evaluation of the biochar’s influence on plant disease suppress: a global meta-analysis

Abstract: Numerous studies have demonstrated that soil applications of biochar contribute to plant disease suppression and growth promotion. Here, we quantitatively evaluated the performance of biochars on plant disease suppression and production using meta-analysis of literature data. The results indicated that biochar amendment dramatically reduced disease severity (DS) by 47.46% while increasing plant biomass by 44.05%. The highest disease suppression was achieved with soil application of straw-derived biochar compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 88 publications
0
4
0
Order By: Relevance
“…The growth and yield of Chenopodium quinoa and lettuce were enhanced by 300% in a hostile loam-sandy soil treated with 2% biochar (Trupiano et al, 2017). Luigi et al (2022) showed that biochar seems to promote the development of the tomato seedlings, especially at concentrations ranging from 1% to 20% (w/w with peat) without showing any antimicrobial effects on the beneficial soil bacteria at the tomato rhizosphere level and even improving their growth, because the application of biochar enhanced the soil pH as well as the retention of both the soil water and nutrients (Yang et al, 2022). Biochar ameliorated substrate characteristics (available N increase of 17% and total C increase 13%), resulting in a promotion effect on plant root, shoot, and leaf morphology, the biochar-treated plants had a greater number of leaves (38 and 68 at the vegetative and fruit stages, respectively) than the untreated plants (32 and 49, respectively).…”
Section: Biochar As a Plant Growth Regulatormentioning
confidence: 99%
“…The growth and yield of Chenopodium quinoa and lettuce were enhanced by 300% in a hostile loam-sandy soil treated with 2% biochar (Trupiano et al, 2017). Luigi et al (2022) showed that biochar seems to promote the development of the tomato seedlings, especially at concentrations ranging from 1% to 20% (w/w with peat) without showing any antimicrobial effects on the beneficial soil bacteria at the tomato rhizosphere level and even improving their growth, because the application of biochar enhanced the soil pH as well as the retention of both the soil water and nutrients (Yang et al, 2022). Biochar ameliorated substrate characteristics (available N increase of 17% and total C increase 13%), resulting in a promotion effect on plant root, shoot, and leaf morphology, the biochar-treated plants had a greater number of leaves (38 and 68 at the vegetative and fruit stages, respectively) than the untreated plants (32 and 49, respectively).…”
Section: Biochar As a Plant Growth Regulatormentioning
confidence: 99%
“…However, the biocontrol effect of biochar on plant diseases was found to vary with the source material (biomass or agro waste) used for making the biochar, the pyrolysis process and the quantity applied to the soil/crops. A recent meta-analysis of the available literature about biochar and its influence on plant pathogen/disease revealed that biochar made with temperatures ranging from 350-600°C was found to have better disease suppression and growth promotion in plants (Yang et al, 2022). Application of 3-5% of biochar was found to decrease diseases by 59%.…”
Section: Biochar In Plant Disease Managementmentioning
confidence: 99%
“…Recent studies had shown that biochar-extract liquor as a DOM (dissolvable organic matter) fraction had been known of a composition of organic compounds as biopolymers, humics, building blocks, low molecular weight acids, and low molecular weight neutrals as well as hydrophobic organic carbon ( Lou et al., 2015 ; Bian et al., 2019 ). Further, labile organic molecules from fast pyrolysis of rice husk are beneficial to improve plant metabolic processes, which directly affect the related gene and protein expression ( Yuan et al., 2017 ; E et al., 2019 ; Yang et al., 2022 ). Several organic matters of biochar including 2-Acetyl-5-methylfuran have been reported to affect the plant growth and development ( E et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%